2015
DOI: 10.5713/ajas.14.0604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary L-carnosine and Alpha-lipoic Acid on Growth Performance, Blood Thyroid Hormones and Lipid Profiles in Finishing Pigs

Abstract: The present study was conducted to determine the effects of L-carnosine (LC) and/or alpha-lipoic acid (ALA) supplementation on growth performance, blood thyroid hormones and lipid profiles in finishing pigs. A total of 40 (Landrace×Yorkshire) pigs with an initial body weight of 57.93±3.14 kg were randomly allocated to 4 experimental diets using a 2×2 factorial arrangement with 2 LC supplemental levels (0 or 0.1%) and 2 ALA supplemental levels (0 or 0.03%) in basal diets. The results showed that pigs fed LC-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…The present result indicated that dietary addition of L-CAR improved the ADG of pigs at the body weight of 50-75 kg, which was consistent with the result of Bao et al (16) showing dietary supplementation with carnosine presented beneficial effect on growth performance of finishing pigs. In addition, dietary L-histidine supplementation significantly decreased the ADFI of pigs compared with the L-carnosine supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…The present result indicated that dietary addition of L-CAR improved the ADG of pigs at the body weight of 50-75 kg, which was consistent with the result of Bao et al (16) showing dietary supplementation with carnosine presented beneficial effect on growth performance of finishing pigs. In addition, dietary L-histidine supplementation significantly decreased the ADFI of pigs compared with the L-carnosine supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…The higher body weight gain in Cndp1 -KO mice is probably caused by higher food intake as compared to WT mice. Carnosine supplemented pigs achieve greater body weight gain together with an increased food intake [ 45 ] and carnosine treated STZ mice experience 50% less body weight loss than STZ mice without carnosine supplementation [ 42 ]. Cndp1 -KO zebra fish have increased carnosine concentrations, and exhibit less body weight gain with high-fat diet than the respective WT fish [ 46 ] and a combination of genetic variations in CNDP1 and CNDP2 were associated with obesity risk in Japanese men [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent papers have attracted the interest of the swine industry on the advantages of increasing muscle carnosine to improve pigs growing performances and meat quality. In the first paper, dietary supplementation of carnosine was found to increase pigs average daily gain, average daily feed intake and live weight [ 12 ] and, in the second paper, pigs with high muscle carnosine content had improved water holding capacity and meat color values [ 13 ]. The oxidative status of pigs skeletal muscle can greatly impact meat quality and carnosine was recently reported to improve the antioxidant capacity in skeletal muscles of pigs supplemented with carnosine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of satellite/myoblast cells proliferation and fusion in supporting hypertrophy of existing muscle fibers during postnatal growth was demonstrated recently [ 15 ] as well as their key roles in muscle regeneration [ 16 ]. The carnosine ability to improve pig growing performances [ 12 ] could be explained, at least in part, by its effect on myoblasts replicative capacity. This was indeed demonstrated by Maier et al [ 17 ] reporting an increase in human myoblasts proliferation after addition of carnosine, 30 days upon establishment of cell cultures.…”
Section: Introductionmentioning
confidence: 99%